Experimental study on the effect of SO2 on PCDD/F emissions: determination of the importance of gas-phase versus solid-phase reactions in PCDD/F formation - Ryan, Shawn P; Li, Xiao-Dong; Gullett, Brian K; Lee, C W; Clayton, Matt; Touati, Abderrahmane (Environmental science & technology, 2006)
Cofiring coal in municipal solid waste incinerators (MSWls) has previously been reported to reduce polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDDs/Fs) emissions due to increasing the flue gas SO2 concentration. The present study was focused on understanding the primary mechanism responsible for the suppressant effect of SO2 on total PCDD/F formation and toxic equivalent (TEQ) emissions. The addition of SO2, simulating the effect of coal addition on the flue gas composition, resulted in significant reductions in the TEQ emissions due to reactions involving SO2 in the postcombustion zone. However, emissions of total PCDDs/Fs, unlike the TEQ value, were dependent upon the Cl2 and SO2 injection temperatures due to increases in non-TEQ correlated isomers. The conversion of metal chlorides in the fly ash to sulfates, thus reducing the sites responsible for chlorination/oxidation reactions, was concluded to be the main suppressant mechanism; proposed reactions for copper and iron are presented. This mechanism was found to be independent of combustion conditions and could have prolonged effects on PCDD/F emissions from deposits formed with high flue gas S/Cl ratios.